Young's modulus and creep compliance of GaAs and Ga1-xMnxAs ferromagnetic thin films under thermal stress at varied manganese doping levels - Kemei, S. K.; Kirui, M. S. K.; Ndiritu, F. G.; Ngumbu, R. G.; Odhiambo, P. M.; Leite, D. M. G.; Pereira, A. L. J.; Dias da Silva, J. H. [UNESP] (De Gruyter Open Ltd, 2015)
Dynamical mechanical analysis yields information about the mechanical properties of a material as a function of deforming factors, such as temperature, oscillating stress and strain amplitudes. GaAs and Mn-doped GaAs at varied levels, used in making electronic devices, suffer from damage due to changes in environmental temperatures. This is a defective factor experienced during winter and summer seasons. Hence, there was a need to establish the best amount of manganese to be doped in GaAs so as to obtain a mechanically stable spin injector material to make electronic devices. Mechanical properties of Ga1-xMnxAs spin injector were studied in relation to temperatures above room temperature (25 degrees C). Here, creep compliance, Young's moduli and creep recovery for all studied samples with different manganese doping levels (MDLs) were determined using DMA 2980 Instrument from TA instruments Inc. The study was conducted using displace-recover programme on DMA creep mode with a single cantilever clamp. The samples were prepared using RF sputtering techniques. From the creep compliance study it was found that MDL of 10 % was appropriate at 30 degrees C and 40 degrees C. The data obtained can be useful to the spintronic and electronic device engineers in designing the appropriate devices to use at 30 degrees C and above or equal to 40 degrees C.
Keywords: creep compliance; Young's modulus; percentage creep recovery; strain jumps; manganese doping levels